2020
DOI: 10.1063/5.0028002
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of XAS theory for unraveling structural changes of adsorbates: CO on Ni(100)

Abstract: Studying surface reactions using ultrafast optical pump and x-ray probe experiments relies on accurate calculations of x-ray spectra of adsorbates for the correct identification of the spectral signatures and their dynamical evolution. We show that experimental x-ray absorption can be well reproduced for different binding sites in a static prototype system CO/Ni(100) at a standard density functional theory generalized-gradient-approximation level of theory using a plane-wave basis and pseudopotentials. This va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In contrast the Z + 1 approximation does predict the correct order (with the exception of CH 3 OH and CH 3 Cl which are very close in energy) with a MAD of 0.14 eV. This is consistent with previous findings that have highlighted the merits of the Z + 1 approach 68 …”
Section: X‐ray Photoelectron Spectroscopysupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast the Z + 1 approximation does predict the correct order (with the exception of CH 3 OH and CH 3 Cl which are very close in energy) with a MAD of 0.14 eV. This is consistent with previous findings that have highlighted the merits of the Z + 1 approach 68 …”
Section: X‐ray Photoelectron Spectroscopysupporting
confidence: 90%
“…In the Z + 1 approximation, the core‐ionized state is described by the system where the core‐ionized atom is replaced by the valence ionized atom with one greater nuclear charge 65 . This approach has been shown to be successful in predicted the core‐level energy shifts, and studies detailing comparison with ΔSCF calculations have been reported 66‐68 . Table 3 shows computed core‐level shifts for the carbon atom in a range of chemical environments and compares the core‐level shifts determined from the Kohn–Sham (‐ε i KS ) and Hartree–Fock (‐ε i HF ) eigenvalues and the Z + 1 approximation with those from ΔSCF.…”
Section: X‐ray Photoelectron Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…To interpret the time evolution of the spectra, we perform density functional theory (DFT) calculations using the Quantum ESPRESSO [42,43] code, with spectra calculated using the xspectra [44][45][46] code. The general method for spectral calculation and treatment of the core-hole has been described elsewhere [47]. A 4 × 4 × 4 periodic slab was used for all spectrum calculations with a single CO molecule adsorbed at an on-top site, corresponding to ¼ ML coverage instead of the experimental 0.66 ML.…”
mentioning
confidence: 99%
“…In spite of successful application to large molecules [45][46][47] and extended systems, [48][49][50] TP-DFT is essentially a ground state theory for XAS. A different approach is to use the equation of motion describing the linear response of the electron system to an applied electromagnetic field.…”
Section: Linear Response Methodsmentioning
confidence: 99%